Respuesta :

Answer:

d) [tex]8g^{6}h^{4} k^{12} - (h^{25} k^{15} )[/tex]

      [tex]\frac{(4g^{3} h^{2}k^{4} )^{3} }{8g^{3}h^{2} } - (h^{5} k^{3} )^{5}[/tex]    [tex]= 8g^{6}h^{4} k^{12} - (h^{25} k^{15} )[/tex]

Step-by-step explanation:

Explanation

Given expression

           =     [tex]\frac{(4g^{3} h^{2}k^{4} )^{3} }{8g^{3}h^{2} } - (h^{5} k^{3} )^{5}[/tex]

By using

        (ab)ⁿ = aⁿbⁿ

         [tex]\frac{a^{m} }{a^{n} } = a^{m-n}[/tex]

   =     [tex]\frac{(4)^{3} g^{9} h^{6}k^{12} ) }{8g^{3}h^{2} } - (h^{5} k^{3} )^{5}[/tex]

After simplification , we get

  [tex]= 8g^{9}g^{-3} h^{6} h^{-2} k^{12} - (h^{5} k^{3} )^{5}[/tex]

 [tex]= 8g^{9-3}h^{6-2} k^{12} - (h^{5} k^{3} )^{5}[/tex]

[tex]= 8g^{6}h^{4} k^{12} - (h^{25} k^{15} )[/tex]